Downregulation of Bcl-2 Expression by miR-34a Mediates Palmitate-Induced Min6 Cells Apoptosis - Xiaojie Lin; Hongyu Guan; Zhimin Huang; Juan Liu; Hai Li; Guohong Wei; Xiaopei Cao; Yanbing Li (Journal of Diabetes Research)
Recent studies have demonstrated that the expression of miR-34a is significantly upregulated and associated with cell apoptosis in pancreatic β-cell treated with palmitate. Nevertheless, the underlying detailed mechanism is largely unknown. Here, we showed that miR-34a was significantly induced in Min6 pancreatic β-cell upon palmitate treatment. Elevated miR-34a promoted Min6 cell apoptosis. Intriguingly, ectopic expression of miR-34a lowered the expression of Bcl-2, an antiapoptotic protein. Luciferase reporter assay indicated the direct interaction of miR-34a with the Bcl-2 3′-UTR. Moreover, downregulated expression of Bcl-2 induced by palmitate could be restored by inhibition of miR-34a. We conclude that direct suppression of Bcl-2 by miR-34a accounts for palmitate-induced increased apoptosis rate in pancreatic β-cell.